(untitled) (TEL Tempo, Espaço e Linguagem, 2024)
As part of the global influx of industrial geography, the city of Luanda was seen as a center for the formation of new consumer goods, and its food profile was closely observed by the colonial administration from the 1950s onwards. In this sense, this article focuses on the spatial and symbolic strategies used by Portuguese colonialism to shape the eating habits of the urban space of Luanda. The analysis of the information collected from different types of sources reveals a dialectic of change flanked by local subjectivities As part of the global influx of industrial geography, the city of Luanda was seen as a center for the formation of new consumer goods, and its food profile was closely observed by the colonial administration from the 1950s onwards. In this sense, this article focuses on the spatial and symbolic strategies used by Portuguese colonialism to shape the eating habits of the urban space of Luanda. The analysis of the information collected from different types of sources reveals a dialectic of change flanked by subjectivities and local contingencies. .